'Whose life are They Going to Save? It's Probably Not Going to be Mine!' Living With a Life-Shortening Condition During the Coronavirus (COVID-19) Pandemic: A Grounded Theory Study of Embodied Precarity. (December 2022) - Earle, Sarah; Blackburn, Maddie; Chambers, Lizzie; Downing, Julia; Flemming, Kate; Hale, Jamie; Marston, Hannah R.; O'Dell, Lindsay; Sinason, Valerie; Watts, Lucy; Whitney, Sally
This article explores the experiences of young adults with a life-shortening condition in the first wave of the Coronavirus (COVID-19) pandemic in the UK. It presents the findings from an inclusive qualitative research study using constructivist grounded theory which aimed to examine the unintended consequences of pandemic control measures (lockdown and 'shielding') on this population. Purposive and theoretical sampling methods were used to recruit young adults with a life-shortening condition, employing a range of recruitment methods such as social media, advertising in newsletters and snowballing. Twenty-six young adults (aged 22–40 years), with a wide range of life-shortening conditions participated in the study. Seventeen participants were female and nine male. The majority identified as White British/Other and the remainder as Black British (2), Mixed Race (2) or Latin American (1). Data were generated iteratively using in-depth guided interviews and analysed collectively by an inclusive research team using the constant comparative method. The article explores a theory of embodied precariousness of living with a life-shortening condition during the first wave of the Coronavirus pandemic in relation to three categories: the rationing of life-saving treatment, the deterioration of health and retraction of healthcare provision, and the disruption of typical care arrangements. The findings show that the pandemic control measures introduced to keep people safe have intensified the precarity of this group promoting inequalities in healthcare and health outcomes. The article identifies some implications for practice to support the future management of unexpected and unwanted change.